The judicial decision as an act of love - Coaguila Valdivia, Jaime Francisco (2007)
The present essay is a reconstruction of the concept of justice through the alterity, the narrativity and the love; with the purpose to contribute to the formulation of a poetic of the justice where the judge veredict can be converted into an act of love for the fellow being